The Impact of an Internet-Based Computer Laboratory on Graduate Students’ Learning of Econometrics (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
With an increased use of modern ICT methodologies in teaching econometrics, additional research is needed to evaluate their effects on students’ learning of econometrics. The purpose of this paper is to empirically investigate how the Internet-based computer laboratory at Ss. Cyril and Methodius University in Skopje, Faculty of Economics influenced graduate students’ learning of the subject Econometrics. This paper summarizes both teachers’ and students’ experiences in the teaching-learning process of Econometrics at graduate level in a computer laboratory. Teaching and learning econometrics in a computer lab has advantages and disadvantages for both, teachers and students. However, in this paper we have shown that the benefits of the computer laboratory outweigh its drawbacks and conclude that the computer laboratory at the Faculty of Economics-Skopje has been successfully used both for teaching and learning of Econometrics.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.